2017
DOI: 10.1136/gutjnl-2017-314903
|View full text |Cite
|
Sign up to set email alerts
|

Adherent-invasive Escherichia coli in inflammatory bowel disease

Abstract: Intestinal microbiome dysbiosis has been consistently described in patients with IBD. In the last decades, Escherichia coli, and the adherent-invasive E coli (AIEC) pathotype in particular, has been implicated in the pathogenesis of IBD. Since the discovery of AIEC, two decades ago, progress has been made in unravelling these bacteria characteristics and its interaction with the gut immune system. The mechanisms of adhesion of AIEC to intestinal epithelial cells (via FimH and cell adhesion molecule 6) and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
318
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(347 citation statements)
references
References 215 publications
12
318
0
1
Order By: Relevance
“…In IBDs, there is a significant reduction in beneficial bacteria, including Firmicutes, Bacteroidetes, Actinobacteria, and Verrucomicrobia, with a concomitant increase in anaerobic bacteria of the family Enterobacteriaceae, playing a pathogenic role in the inflamed colon (Zuo & Ng, ). Despite there still being no identification of causative microorganism in IBDs, multiple studies suggested the involvement of pathogens such as Mycobacterium avium paratuberculosis , Clostridium difficile , and Helicobacter and altered commensals such as adherent‐invasive E. coli (Issa et al, ; Thomson et al, ; Nazareth et al, ; Palmela et al, ), whereas case report studies indicated the inflamed colon as a favorable environment for infection of different opportunistic pathogens, including P. aeruginosa and S. aureus (Bettenworth et al, ; Iguidbashian et al, ). A great deal of interest also emerged as regards the involvement of fungi in colon inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…In IBDs, there is a significant reduction in beneficial bacteria, including Firmicutes, Bacteroidetes, Actinobacteria, and Verrucomicrobia, with a concomitant increase in anaerobic bacteria of the family Enterobacteriaceae, playing a pathogenic role in the inflamed colon (Zuo & Ng, ). Despite there still being no identification of causative microorganism in IBDs, multiple studies suggested the involvement of pathogens such as Mycobacterium avium paratuberculosis , Clostridium difficile , and Helicobacter and altered commensals such as adherent‐invasive E. coli (Issa et al, ; Thomson et al, ; Nazareth et al, ; Palmela et al, ), whereas case report studies indicated the inflamed colon as a favorable environment for infection of different opportunistic pathogens, including P. aeruginosa and S. aureus (Bettenworth et al, ; Iguidbashian et al, ). A great deal of interest also emerged as regards the involvement of fungi in colon inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…The question to which; however, it is not yet possible to give a definitive answer is whether AIEC is the primary cause of IBS or whether it can only exacerbate the disease. The high presence of E. coli in the faeces of healthy people, able to invade epithelial cells or to replicate within macrophages, or to do both (AIEC), supports the emerging view that these types of bacteria make normally part of the resident flora, and that, therefore, are pathogenic only in hosts that show a susceptibility (Dogan et al, ; Packey & Sartor, ; Palmela et al, ). Furthermore, studies have shown that persistent intestinal inflammation, in the absence of genetic susceptibility, can induce dysbiosis and excessive proliferation of AIEC within the ileum (Craven et al, ).…”
Section: Ecoli Aiecmentioning
confidence: 78%
“…Some studies in animal models have highlighted the importance of preceding dysbiosis and/or gut inflammation (such as dextran sulfate sodium [DSS] colitis or antibiotic therapy) for successful infection with AIEC (Carvalho et al, ; Drouet et al, ) others, instead, confirmed the pathogenic properties of AIEC and that AIEC infection itself could induce long‐term changes in the gut microbiota, such as the transient colonisation of T5KO mice by AIEC induced intestinal dysbiosis, with a greater proinflammatory potential due to increased levels of LPS and flagellin. These changes in the microbiota could cause chronic inflammation and disease (Palmela et al, ).…”
Section: Ecoli Aiecmentioning
confidence: 99%
See 1 more Smart Citation
“…Более того, в ряде работ было показано, что БК-ассоциированные Escherichia coli обладают способно-стями, кумулятивно позволяющими рассматривать их как потенциальный патогенетический фактор при БК (адгезия к эпителиоцитам слизистой; внедрение в эпителиоциты слизистой; активная репликация внутри макрофагов) [26][27][28]. Частота выявления такого фенотипа Escherichia coli у пациентов с БК на 30% выше, чем у здоровых лиц [29]. Отдельно стоит отметить, что роль альтераций микробиома у пациентов с ВЗК подчеркивается эффективностью транс-плантации фекальной микробиоты у этой категории паци-ентов.…”
Section: этиопатогенезunclassified